Effects on small-intestinal function and structure induced by feeding a deconjugated bile salt. Issue 7 (July 1973) - Gracey, Michael; Papadimitriou, John; Burke, Valerie; Thomas, Jennifer; Bower, Geoffrey
Abstract : Feeding sodium deoxycholate orally to rats for three days caused inhibition of small-intestinal active sugar transport and ouabain-sensitive, sodium-potassium-dependent adenosine triphosphatase activity. At the same time, there was evidence of extensive ultrastructural damage to the microvillar and intracellular compartments of the small-intestinal epithelium while its light microscopic appearance was essentially normal. These functional and morphological changes reverted towards normal over the subsequent four days when a normal diet, without added bile salt, was reintroduced.